TECHNOLOGY INSTALLATION VS. TECHNOLOGY INTEGRATION - Ozden, M. Yasar (Iated-Int Assoc Technology Education & Development, 2015)
Technology is changing everything in our life. In the 21st century our educational paradigm will also be changed as a result of those changes. There have been considerable amount of studies related potential benefits of technology into instructional settings. In addition to research-based findings technological tools have been increasingly utilized in educational settings due to international standards and national polies. However, these standards(ISTE2008, Midoro, 2005) do not make a connection between teachers' technological capabilities and their integration into those settings. Therefore, technology related Professional programs and pre-service teacher education programs focus on only those technological capabilities in practice. However, even using technology occasionally is not adequate because teachers should integrate those capabilities into teaching and learning process for the requirements of successful technology integration (Bose, 2010). Therefore, pre-service teacher education programs aiming to teach only technological capabilities cannot be successful transferring those capabilities into teaching and learning environments (Koc and Bakir, 2010). One of the main reason behind the lack of success of pre-service teacher programs may have been proposed as oversimplification of technology integration by separating technology from pedagogy and content knowledge (The AACTE Committee, 2008). Ethnological Pedagogical Content knowledge (TPACK) provides a framework for programs to focus on using technology, pedagogy and content interactively rather then just using technology (Mishra & Kohler2006, Cox, 2008) Therefore, using this framework may solve technology problems.
8th International Conference of Education, Research and Innovation (ICERI) -- NOV 16-20, 2015 -- Seville, SPAIN
Keywords: technology integration; TPACK